What Are the Drivers of Fiscal Performance Gaps between Anglophone and Francophone Africa? A Blinder–Oaxaca Decomposition. (2nd April 2015) - Sarr, Babacar
Abstract: In this paper, we make use of the Blinder–Oaxaca decomposition to examine how the quality of budget institutions affects fiscal performance – primary balance and public debt – in sub‐Saharan Africa. To organise our approach, we categorise sub‐Saharan Africa countries according to the two main systems of budgetary institutions: the English‐based system and the French‐based system. The quality of budget institutions is measured through five criteria: centralisation, comprehensiveness, fiscal and procedural rules, sustainability and credibility, and transparency. Our findings show that, on average, Anglophone Africa countries have better budgetary institutions than their Francophone counterparts, and this difference is the main determinant of the fiscal performance gaps between the two groups. These performance gaps are mostly due to the characteristics effect, meaning that the relative poor fiscal performance of Francophone countries is not due to the French‐based system itself but rather to the environment in which it operates. The budget process and procedures in these countries are relatively less comprehensive, sustainable and transparent and that adversely affects their fiscal performance.